Training and overtraining markers in selected sport events - Hartmann, U.; Mester, J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Varieties of symptoms are supposed to detect overtraining (OT). Besides the problems of diagnosis and analysis in elite athletes, a daily monitoring of training status takes place with measurement of the parameters serum urea (SU) and serum creatine kinase (CK); therefore, their meaningfulness will be examined, with special respect inter- and intra-individually. Methods: Data were obtained from determinations during training from athletes in rowing and athletes of international level. Results: For 6981 SU determinations (male, N = 717; female, N = 285), a slightly asymmetric normal distribution was found (male, 80%, 5-7 mmol·L-1; female, 75%, 4-6 mmol·L-1). Values for women were approximately 1.5 mmol·L-1 lower. Individual variability was enormous; there seems little point in setting fixed value as 8.3 mmol·L-1 for men and 7.0 mmol·L-1 for women as a critical limit for OT. CK has also been measured and evaluated in sports as an essential parameter for determination of muscular stress. Frequency distributions of CK in 2790 samples (male, N = 497; female, N = 350) presented an asymmetric normal distribution with distinct trend toward higher values being evident for the range between 100 and 250 U·L-1. Conspicuously elevated values occurred in the ranges 250-350 U·L-1 and 1000-2000 U·L-1. Men's maximal values were 3000 U·L-1 and 1150 U·L-1 for women. Individual variability was enormous. Athletes with chronically low CK exhibited mainly low variability; those with chronically higher values exhibited considerable variability. Conclusions: Establishment of both parameters should be useful to determine individual baselines from a large number of samples. Determinations should be made at least every 3 d in standardized conditions. If a large increase is observed in combination with reduced exercise tolerance after a phase of exertion (2-4 d), then the possibility of a catabolic/metabolic activity or insufficient exercise tolerance becomes much more likely.